2019
DOI: 10.3389/fphy.2019.00181
|View full text |Cite
|
Sign up to set email alerts
|

Control Electromagnetic Waves Based on Multi-Layered Transparent Metasurface

Abstract: Metasurface was presented to be the two-dimensional analogs of metamaterials that regulate the beam by adjusting the phase and amplitude of the wavefront. By properly designing and arranging the metasurface elements to form an array, the singularity of the metasurface to the propagation direction of the electromagnetic wave beam can be controlled; such unique electromagnetic properties offer additional opportunities to innovate new antennas. In this paper, we present the design and numerical simulation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Where f is the focal length, and λ 0 is the free-space wavelength [23,24]. A continuous curve of phase shift in the range of −168.5 • to 170.8 • , as shown in Figure 2, can be achieved by changing the width of the metallic patch layer.…”
Section: Model Designmentioning
confidence: 99%
“…Where f is the focal length, and λ 0 is the free-space wavelength [23,24]. A continuous curve of phase shift in the range of −168.5 • to 170.8 • , as shown in Figure 2, can be achieved by changing the width of the metallic patch layer.…”
Section: Model Designmentioning
confidence: 99%
“…Metasurfaces are the two-dimensional structure of metamaterials with a subwavelength scale unit cell with a periodic arrangement [1][2][3]. These exhibit anomalous electromagnetic properties that cannot be found in natural materials, like negative refractive [4,5], superlens [6,7], and reversals of both the Doppler shift and Cherenkov radiation effects.…”
Section: Introductionmentioning
confidence: 99%
“…The research shown that the interaction of electromagnetic waves with inhomogeneous or anisotropic media resulting in spin-orbital angular momentum conversion [6][7]. Metasurface is a two-dimensional material with spatial anisotropy, which converts SAM beams into OAM beams and generates central singularities by adjusting the wavefront phase and amplitude of electromagnetic waves [8][9]. An electromagnetic metasurface is designed and fabricated, and experimentally demonstrated to generate multiple orbital angular momentum vortex beam in radio frequency domain [10].…”
Section: Introductionmentioning
confidence: 99%